Pola Resistensi Salmonella typhi yang Diisolasi dari Ikan Serigala (Hoplias malabaricus) terhadap Antibiotik - Monica, Waode Santa; Mahatmi, Hapsari; Besung, Kerta (Veterinary Science and Medicine Journal; Vol 1 No 2 (2013), 2013)
Normal 0 false false false EN-US X-NONE X-NONE The purpose of this study was to know the resistant pattern of S almonella typhi ( S. typhi ) isolated from wolf fish ( H oplias malabaricus ) to antibiotics in Bali Safari and Marine Park . S. typhi w as isolated from fecal s wab collected from the illness fish . The S. typhi w as confirm ed with Microgen TM GN A ID test ’ s method . The a ntibiotic s ensitivit y of the S. typhi was tested using streptomycin, gentamicin, penicillin, vancomycin, and chloramphenicol according to the Kirby b ouer method . The results showed that the isolate of S. typhi was resistant to penicillin and vancomycin , but sensitive to streptomycin, gentamicin, and chloramphenicol. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Wolf Fish, Salmonella typhi, Antibiotic Resistance